The Influence of Job Training and Work Motivation on Teachers' Performance at SMK Yapin Bekasi, West Java, Indonesia - Abdilah K, Luluh (Yayasan Sinergi Kawula Muda, 2023)
The research aims to determine the impact of training and work motivation on the performance of employees at SMKS YAPIN Bekasi, using a quantitative method with saturated sampling of 60 respondents. Data analysis includes validity test, reliability test, classical assumption test, regression analysis, correlation coefficient analysis, determinant coefficient analysis, and hypothesis testing. The results show that training significantly influences employee performance with a correlation coefficient of 0.599, indicating a moderate relationship. The determinant value is 0.359 or 35.9%, while the remaining 64.1% is influenced by other factors. Hypothesis testing yields a t-count > t-table value (5.697 > 2.001), leading to the rejection of H0 and the acceptance of H1, indicating a significant partial influence of training on employee performance. Work motivation significantly influences employee performance with a correlation coefficient of 0.641, signifying a strong relationship. The determinant value is 0.441 or 41.1%, while the remaining 58.9% is influenced by other factors. Hypothesis testing results in a t-count > t-table value (6.360 > 2.001), leading to the rejection of H0 and the acceptance of H1, indicating a significant partial influence of work motivation on employee performance. Both training and work motivation significantly influence employee performance with a correlation coefficient of 0.687, indicating a strong relationship. The determinant value is 0.472 or 47.2%, while the remaining 52.8% is influenced by other factors such as compensation, work environment, and work discipline. Hypothesis testing yields an F-count > F-table value (25.489 > 2.770), leading to the rejection of H0 and the acceptance of H1, indicating a significant simultaneous influence of training and work motivation on employee performance.